Preparticipation orthopedic screening evaluation - Garrick, J. G. (Clinical Journal of Sport Medicine, 2004)
Objective: To review evidence-based support for the preparticipation orthopedic evaluation. Data Sources/Methods: Articles were reviewed that dealt with the sensitivity, specificity, and predictive value of the components of the standardized preparticipation orthopedic evaluation. In addition, studies describing musculoskeletal conditions/findings predictive of future injuries were sought through a PubMed search. Results: The sensitivity of the evaluation questionnaire appears to be adequate, exceeding 90% in some studies. There is little or no published information documenting that the physical examination (1) approaches the questionnaire in either sensitivity or specificity or (2) identifies elements of value based on their association with future injuries or reinjuries. There are no readily discernible elements even in an expanded examination that are documented as being predictive of future problems. Conclusions: The current questionnaire and examination appear to fulfill adequately both legal and institutional requirements. Practitioners should be aware of the absence of data linking virtually any of the findings on the examination to either an increase or a decrease in the likelihood of future injuries. There is no evidence that increasing the scope of the examination would enhance its predictive value.